Improving neurodevelopment in Zika-exposed children: A randomized controlled trial. - Randall Waechter; Kemi S Burgen; Bianca Punch; Roberta Evans; Karen Blackmon; Trevor Noël; Michelle Fernandes; Barbara Landon (Public Library of Science (PLoS), 2022)
Background While microcephaly is a significant adverse outcome of prenatal exposure to the Zika virus (ZIKV), subtle malformations of cortical development (MCD) have been observed in Zika-exposed children (ZEC), including delays in language, cognition, and motor domains, and visual acuity deficits. Interventions within the first 1,000 days of life can significantly improve developmental outcomes. This study examined a 12-week Responsive Caregiving Intervention on neurodevelopmental outcomes in 24-30-month-old ZEC. Methodology/principal findings A randomized controlled trial was implemented in Grenada, West Indies using an existing ZIKV cohort surveillance study. When children in that study turned 24 months, baseline child neurodevelopmental measures and caregiver interviews were administered. Caregivers who agreed to participate in the 12-week Responsive Caregiving Intervention, implemented when children were 24-30 months of age, were randomly assigned to the Intervention or Waitlist Control group. Children in both groups were re-assessed on the neurodevelopmental measures post-intervention. Conclusions/significance 233 children from the ZIKV surveillance study met inclusion criteria, of which n = 80 declined participation, n = 42 did not complete the Intervention, and n = 72 missed follow-up assessments given strict timelines in the study design. The final sample for analysis was N = 13 children in the Intervention group and N = 26 children in the Control group. A GEE model analysis showed significantly higher language (p = 0.021) and positive behaviour (p = 0.005) scores for children in the Intervention group compared to the Control group. The Intervention had a medium effect on child language (d = 0.66) and a large effect on positive behaviour (d = 0.83). A 12-week Responsive Caregiving Intervention Programme significantly improves language and positive behaviour scores in 30-month-old normocephalic children who were exposed to ZIKV in utero. The programme provides an option for mothers of ZIKV-exposed children who are seeking an evidence-based neurodevelopmental intervention regardless of known impact of the virus on cortical formation. Trial registration The study was registered with clinicaltrials.gov (NCT04697147).